Optimalisasi Dan Pemerataan Pendapatan Petani Pada Usahatani Padi Sistem Bagi Hasil - Tutut Dwi Sutiknjo; Widi Artini (Kadiri University, 2019)
The production sharing system for food crops that have been regulated in the UUBH for a long time is still not implemented by all parties. From the existing production function, it can be seen whether the production factors usage has been optimal or not, if it is not optimal, how much is the production factors usage for optimal use. The data collection method was proportionate stratified random sampling with soil class strata as many as 90 respondents who implemented the profit-sharing system of Cultivator Owners, Maro, and Mertelu in Sembon Village, Karangrejo District, Tulungagung Regency. Data were analyzed using multiple regression analysis, efficiency index formula, and Gini Ratio. The results showed that there was a significant effect on the production factors usage with the product produced by the Cobb-Douglas production function estimation model. For the owner cultivator system: R2 = 91.10%; for the Maro system: R2 = 89.07%; for the Mertelu system: R2 = 85.46%. The production process for all production-sharing systems can physically be considered to be in the rational area, for the tenant owner system; Ʃbi = 1.1076; for the Maro system: Ʃbi = 1.0430; for the Mertelu system: Ʃbi = 1.0832. The production factors used for the entire Profit Sharing system is efficient because the Efficiency Index = 1. Productivity, there is no significant difference between the Cultivator Owners, Maro and Mertelu system. Income equalization in the Cultivator System is high on the inequality scale, while for the Maro and Mertelu systems it is low.Sistem bagi hasil untuk tanaman pangan yang sudah lama diatur dalam UUBH sampai saat ini masih belum diterapkan oleh semua pihak. Dari fungsi produksi yang ada dapat diketahui apakah penggunaan faktor produksi sudah optimal atau belum, jika belum optimal seberapa banyak penggunaan faktor produksi agar penggunaannya menjadi optimal. Metode pengambilan data secara proportionate stratified random sampling dengan strata kelas tanah sebanyak 90 responden yang melaksanakan sistem bagi hasil Pemilik Penggarap, Maro, dan Mertelu di Desa Sembon kecamatan Karangrejo Kabupaten Tulungagung. Data dianalisis menggunakan analisis regresi berganda, rumus Index efisiensi, dan Gini Ratio. Hasil penelitian menunjukkan ada pengaruh yang nyata penggunaan faktor produksi dengan produk yang dihasilkan dengan model dugaan dari fungsi produksi Cobb-Douglas, Untuk sisem pemilik penggarap: R 2 = 91,10%; untuk sistem Maro: R2 = 89,07%; untuk sistem Mertelu: R2 = 85,46%. Proses produksi untuk semua sistem bagi hasil secara fisik dapat dianggap berada dalam daerah rasional, untuk sisem pemilik penggarap ; Ʃbi = 1,1076; untuk sistem Maro : Ʃbi = 1,0430; untuk sistem Mertelu : Ʃbi = 1,0832. Penggunaan faktor produksi untuk seluruh sistem Bagi Hasil sudah efisien karena Indeks Efisiensinya = 1. Produktivias tidak ada perbedaan yang nyata antara sistem bagi Pemilik Penggarap, Maro dan Mertelu. Pemerataan pendapatan pada sistem Pemilik Penggarap pada skala ketimpangan tinggi, sedang untuk sistem Maro dan Mertelu ketimpangannya rendah.